Nasal polypectomy and endoscopic sinus surgery for the management of ethmoidal polyp (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: The efficacy of sinus surgery for the treatment of ethmoidal polyp continues to be an issue of debate among otolaryngologists. A study was undertaken to compare the efficacy of Functional Endoscopic Sinus Surgery (FESS) over intra nasal polypectomy in treatment of ethmoidal polyp.Methods: Sixty patients of either sex above 18 years of age suffering from ethmoidal polyp were included in the study. The patients were discharged after surgery and were called for endoscopic examination during subsequent follow up.Results: Final results were recorded 6 months after the operative procedure. The results suggest that FESS is highly effective for the treatment of ethmoidal polyp with the recurrence rate being as low as 10% and with no major complications.Conclusion: This study will help in evaluation of FESS as better surgical option for the management of ethmoidal polyp DOI: http://dx.doi.org/10.3329/bjo.v18i2.12008 Bangladesh J Otorhinolaryngol 2012; 18(2): 161-165